Coordination Chemistry of Cyclopropenylidene‐Stabilized Phosphenium Cations: Synthesis and Reactivity of Pd and Pt Complexes. Issue 8 (23rd January 2014) - Kozma, Ágnes; Deden, Tobias; Carreras, Javier; Wille, Christian; Petuškova, Jekaterina; Rust, Jörg; Alcarazo, Manuel
Abstract A straightforward synthesis of cyclopropenylidene‐stabilized phosphenium cations 1 a–g through the reaction of [(iPr2N)2C3+Cl]BF4 with secondary phosphines is described. Their donor ability was evaluated by analysis of the CO stretching frequency in Rh complexes [RhCl(CO)L2](BF4)2 and electrochemical methods. The cyclopropenium ring induces a phosphite‐type behavior that can be tuned by the other two substituents attached to the phosphorus atom. Despite of the positive charge that they bear, phosphenium cations 1 a–g still act as two‐electron donor ligands, forming adducts with PdII and PtII precursors. Conversely, in the presence of Pd0 species, an oxidative insertion of the Pd atom into the Ccarbene–phosphorus bond takes place, providing dimeric structures in which each Pd atom is bonded to a cyclopropenyl carbene while two dialkyl/diaryl phosphide ligands serve as bridges between the two Pd centers. The catalytic performance of the resulting library of PtII complexes was tested; all of the cationic phosphines accelerated the prototype 6‐endo‐dig cyclization of 2‐ethynyl‐1, 1′‐biphenyl to afford pentahelicene. The best ligand 1 g was used in the synthesis of two natural products, chrysotoxene and epimedoicarisoside A.